Determinants of occupational accidents in the woodworking sector: the case of the Malaysian wooden furniture industry - Ratnasingam, Jegatheswaran; Ioras, Florin; Swan, T. T.; Yoon, C. Y.; Thanasegaran, Ganesh (Asian Network for Scientific Information, 2011)
Studies on occupational accidents in the value-added wood products industry, particularly the wooden furniture industry is grossly lacking. Therefore, the risk factors for injuries to workers in the Malaysian wooden furniture industry were studied in fifty wood-furniture manufacturing factories, using a structured questionnaire. The three primary risk factors for accidents in the wooden furniture industry were: Nature of work, workers characteristics and prevailing safety climate, while the use of dangerous machinery and poor layout were found to be secondary accident causing risk factors. The findings of the study show conclusively that the prevailing safety climate and workers’ characteristics have the strongest influence on accident rate in the wooden furniture industry. It must also be recognized that the production oriented mentality prevalent in the industry appears to contribute towards the compromised occupational safety and health standards in the industry. In this context, it is essential for the policy makers to implement binding legislations that would safe guard the safety and health of the workers, while mandating the factory management to show commitment towards the workers health and safety to ensure a safe working environment in the wooden furniture manufacturing industry.